Simultaneous measurement of temperature and strain using a phase-shifted fiber Bragg grating inscribed by femtosecond laser. (26th February 2018) - Jiang, Yajun; Liu, Chi; Li, Dong; Yang, Dexing; Zhao, Jianlin
Abstract: A novel method for simultaneous measurement of temperature and strain using a single phase-shifted fiber Bragg grating (PS-FBG) is proposed. The PS-FBG is produced by exposing the fusion-spliced fiber with a femtosecond laser and uniform phase mask. Due to the non-uniform structure and strain distribution in the fusion-spliced region, the phase-shift changes with different responses during increases to the temperature and strain; by measuring the central wavelengths and the loss difference of two transmission dips, temperature and strain can be determined simultaneously. The resolutions of this particular sensor in measuring temperature and strain are estimated to be  ±1.5 °C and  ±12.2 µε in a range from  −50 °C to 150 °C and from 0 µε to 2070 µε .